Persepsi Guru dalam Penerapan Pembelajaran Problem Based Learning terhadap Penguasaan Konsep dan Keterampilan Pemecahan Masalah IPA Siswa SD di Kelas Tinggi - Pujawati, Sri Ayu; Jayadinata, Asep Kurnia; Sudin, Ali (Jurnal Pena Ilmiah, 2021)
This research is based on the researcher’s interest in concepts mastery and problem solving skills of students. Application of problem based learning into learning is an appropriate way to improve students' concepts mastery and problem solving skills. Research purposes is to study the teachers' perceptions of the effect of problem based learning models on concepts mastery and problem solving skills. This research used method quantitative descriptive research and used survey for research design. High grade teachers in elementary schools in North Sumedang District became the research population. questionnaire is the instrument. The research discovered that the PBL learning model had a positive influence on concepts mastery and problem solving skills of students with a strong position. The implication of the research is that when teachers wanted to improve concepts mastery and problem solving skills of students they could applied the PBL model as a strategy.